Development of high-performance microbial fuel cells by enhancing extracellular electron transfer between bacteria and electrode materials - Yu, Yang-Yang (2015)
The microbial fuel cell (MFC) is a novel biotechnology that combines wastewater treatment and energy harvest. Traditional MFCs usually consist of a bioanode in which bacteria community attached on the anode (known as biofilm) degrade organic carbon sources and transfer the electrons generated from intracellular metabolisms to electrodes. These electrons will pass through an external resistance and reach chemical or oxygen cathodes to complete electricity circuits. Many efforts have been done to improve the anode and cathode efficiency. For MFCs anode, material science development and reactor operation optimization greatly have improved the system performance in the past decade. Many studies on extracellular electron transfer (EET) mechanisms also have been done and two possible EET pathways were elucidated. The cathode development mainly focuses on investigating suitable materials and reactions to simultaneously meet the requirement on high performance and low cost. The recent development in biocathode opens the door to utilize electron generated from anode for more sophisticated application in bioremediation and bioproduction. In this thesis, we implemented a number of researches aiming at the improvement of anode performances. Different strategies were developed to improve the extracellular electron transfer and thus bioelectricity and power output. In the first work, I rationally designed a conductive artificial biofilm (CAB) which immobilized Shewanella oneidensis MR-1 into the graphite and polypyrrole matrix. In this way the biomass loading amount was greatly increased compared with naturally occurring biofilms on carbon cloth electrode. Anode performance with such CAB- equipped MFCs was greatly enhanced. In the second work, we developed an anode modification with nitrogen doped carbon nanoparticle. Cyclic Voltammetry analysis reveals that the modified electrode has the capability to retention soluble mediator flavins compared with former reported CNT. This greatly increased the MET in MFCs anode and also inspired rational design novel composite material for future applications. The bioelectrochemical behavior of Pseudomonas aeruginosa PAO-1 with global regulator mutation was studied in the third work. We demonstrate here that such upstream regulator random mutation is potential effective tool for improve the system performance. In the last work, we successfully developed synthesized ecosystem composes of Shewanella oneidensis MR-1 and Pseudomonas aeruginosa PAO-1. Maximum power density of 523.5 mW/m2 was achieved, which was the best performance in all these works.